2002
DOI: 10.1517/14656566.3.9.1301
|View full text |Cite
|
Sign up to set email alerts
|

Alternative and rescue treatment regimens for Helicobacter pylori eradication

Abstract: Eradication therapy has been incorporated into clinical practice. The regimens currently recommended for first-line treatment include a 2-week bismuth-based triple therapy (mainly in developing countries), a 1 - 2 week proton pump inhibitor (PPI)-based triple therapy and a 1-week ranitidine bismuth citrate (RBC)-based triple therapy. However, these regimens fail to eradicate Helicobacter pylori in up to 20% of patients due to poor compliance, inadequate treatment duration, smoking, old age and bacterial resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(1 citation statement)
references
References 106 publications
0
1
0
Order By: Relevance
“…Triple therapy consisting of amoxicillin, clarithromycin (CAM) and a proton pump inhibitor has proven to be effective for the eradication of H. pylori so far. 9) As in the case of other bacteria, however, there has been an increase in the appearance of drug-resistant strains of H. pylori. It has been reported that failure of eradication of H. pylori infection with triple therapy was approximately 20% of infected patients in Japan.…”
mentioning
confidence: 99%
“…Triple therapy consisting of amoxicillin, clarithromycin (CAM) and a proton pump inhibitor has proven to be effective for the eradication of H. pylori so far. 9) As in the case of other bacteria, however, there has been an increase in the appearance of drug-resistant strains of H. pylori. It has been reported that failure of eradication of H. pylori infection with triple therapy was approximately 20% of infected patients in Japan.…”
mentioning
confidence: 99%